2009
DOI: 10.1007/s10683-009-9232-x
|View full text |Cite
|
Sign up to set email alerts
|

Fragility of information cascades: an experimental study using elicited beliefs

Abstract: This paper examines the occurrence and fragility of information cascades in two laboratory experiments. One group of low informed participants sequentially guess which of two states has been randomly chosen. In a matched pairs design, another group of high informed participants make similar guesses after having observed the guesses of the low informed participants. In the second experiment, participants' beliefs about the chosen state are elicited. In equilibrium, low informed players who observe an establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 24 publications
0
16
0
2
Order By: Relevance
“…• Do you have any comments about this experiment? 21 We found that the answers, especially to the first question, provide an insight into the decision rules employed by the participants. As far as we know, we are the first to explore the possibility and the usefulness of asking directly participants to explain how they reached decisions.…”
Section: Heterogeneous Decision Rulesmentioning
confidence: 88%
“…• Do you have any comments about this experiment? 21 We found that the answers, especially to the first question, provide an insight into the decision rules employed by the participants. As far as we know, we are the first to explore the possibility and the usefulness of asking directly participants to explain how they reached decisions.…”
Section: Heterogeneous Decision Rulesmentioning
confidence: 88%
“…On the other hand, the ZM K meta-dataset includes all 1,440 observations from Ziegelmeyer, Koessler, Bracht, and Winter (2010) as well as the 1,080 individual observations from the P IT treatment of Fahr and Irlenbusch (2011).…”
Section: A New Meta-dataset Of Information Cascade Experimentsmentioning
confidence: 99%
“…The studies by Mason and Phillips (2001), Nyarko and Schotter (2002), Camerer, Ho, Chong and Weigelt (2002, expands on a 1988 talk), Ehrblatt, Hyndman, Ozbay and Schotter (2006), Rutstrom and Wilcox (2007), Fehr and Kübler (2007), and Palfrey and Wang (2007) elicit beliefs in repeated games, while Haruvy (2002), Bhatt and Camerer (2005), Ivanov (2006) and Rey Biel (2007) discuss elicited beliefs in normal‐form games. Some studies on cascade game experiments also elicit beliefs; see Ziegelmeyer, Bracht, Koessler and Winter (2002), and Dominitz and Hung (2004).…”
mentioning
confidence: 99%